Physical activity and sedentary behavior among university students : association with anxiety and stress - Ingibjörg Sigfúsdóttir 1993- (2019)
There has been an increasing interest in mental health among university students. Recent studies have shown that sedentary behavior increases symptoms of anxiety and stress and physical activity decreases symptoms of anxiety and stress. However, physical activity and sedentary behavior have not been examined simultaneously among Icelandic university students before. Thus, the aim of this study was to examine if physical activity and sedentary behavior were associated with symptoms of anxiety and stress among university students. Psychology students (N=59) at the Reykjavik University participated in the study, 51 females and 8 males. Stress among participants was assessed using PSS-10 and anxiety was assessed using GAD-7. The results showed that 73% of the students did not meet the recommended weekly physical activity and 44% were sedentary for six hours or more per day. The majority of the students experienced moderate symptoms of stress and mild symptoms of anxiety. However, physical activity and sedentary behavior were not associated with symptoms of anxiety or stress. Yet, students who met recommended weekly physical activity showed less symptoms of anxiety and stress compared to those who did not meet weekly physical activity. Further intervention should be done to encourage university students to increase physical activity and reduce sedentary behavior. Keywords: physical activity, sedentary behavior, mental health, anxiety, stress, university students Á síðustu árum hefur áhugi um andlega heilsu meðal háskólanema aukist til muna. Rannsóknir hafa sýnt að kyrrseta eykur einkenni kvíða og streitu á meðan hreyfing dregur úr einkennum kvíða og streitu. Aftur á móti hefur hreyfing og kyrrseta ekki verið skoðuð samtímis meðal íslenskra háskólanema áður. Markmið þessarar rannsóknar var því að skoða hreyfingu og kyrrsetu meðal háskólanema og hugsanleg tengsl við kvíða og streitu. Sálfræðinemendur (N=59) við Háskólann í Reykjavík tóku þátt í rannsókninni, 51 konur og 8 karlar. Streita var metin með kvarðanum ...